2021
DOI: 10.3390/su13010413
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Circular Bioeconomy: Drivers and Indicators

Abstract: The EU’s 2018 Bioeconomy Strategy Update and the European Green Deal recently confirmed that the bioeconomy is high on the political agenda in Europe. Here, we propose a conceptual analysis framework for quantifying and analyzing the development of the EU bioeconomy. The bioeconomy has several related concepts (e.g., bio-based economy, green economy, and circular economy) and there are clear synergies between these concepts, especially between the bioeconomy and circular economy concepts. Analyzing the driving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(131 citation statements)
references
References 77 publications
1
103
0
5
Order By: Relevance
“…This study analyzed most of the bioeconomy sectors studied to date. Nevertheless, it is important to note that recently published work expands the number of sectors included as bioeconomy sectors [59].…”
Section: Discussion and Conclusive Remarksmentioning
confidence: 99%
“…This study analyzed most of the bioeconomy sectors studied to date. Nevertheless, it is important to note that recently published work expands the number of sectors included as bioeconomy sectors [59].…”
Section: Discussion and Conclusive Remarksmentioning
confidence: 99%
“…(Bio)circularity metrics are important for assessing the effects of a circular (bio)economy in terms of profitability, job creation, and environmental impacts. Circularity should also include some environmental and sustainability elements, including some life cycle environmental impact categories and new socioeconomic indicators (D'Adamo et al, 2020;Kardung et al, 2021). The metrics should help identify which (bio)circular attributes and options are better than others.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…For the bioeconomy, several studies (Sheppard et al 2011;Talavyria et al 2015;Wesseler and von Braun 2017) have identified the main forces driving the development of the bioeconomy and related phenomena. Kardung et al (2021) summarized these forces by grouping them as supply drivers (technology and innovation, markets, and climate change adaption), demand drivers (consumer preferences, economic development, and demography), resource availability, and government measures. Researchers should not disregard detailed descriptions of context to ensure the robustness and generalizability of their findings.…”
Section: Case Study Researchmentioning
confidence: 99%
“…The bioeconomy is a main alternative to fossil materials to address these challenges (European Commission 2018). Several national strategies and policies for bioeconomic development worldwide confirm its key role (Staffas et al 2013;Kardung et al 2021). Increasingly transformative policy initiatives, such as the European Green Deal or the target of net-zero emissions in the European Union (EU) by 2050 (European Commission 2019), require intense efforts and coordination to exploit the bioeconomy and available synergies in all sectors and policy areas.Given the contemporary, context-dependent nature of related phenomena, the scientific case study research method plays a crucial role in developing the bioeconomy.…”
mentioning
confidence: 99%